Pain management with acupuncture in osteoarthritis: a systematic review and meta-analysis - Manyanga, Taru (BioMed Central, 2014)
BACKGROUND: The utility of acupuncture in managing osteoarthritis symptoms is uncertain. Trial results are conflicting and previous systematic reviews may have overestimated the benefits of acupuncture. METHODS: Two reviewers independently identified randomized controlled trials (up to May 2014) from multiple electronic sources (including PubMed/Medline, EMBASE, and CENTRAL) and reference lists of relevant articles, extracted data and assessed risk of bias (Cochrane’s Risk of Bias tool). Pooled data are expressed as mean differences (MD), with 95% confidence intervals (CI) (random-effects model). RESULTS: We included 12 trials (1763 participants) comparing acupuncture to sham acupuncture, no treatment or usual care. We adjudicated most trials to be unclear (64%) or high (9%) risk of bias. Acupuncture use was associated with significant reductions in pain intensity (MD -0.29, 95% CI -0.55 to -0.02, I(2) 0%, 10 trials, 1699 participants), functional mobility (standardized MD -0.34, 95% CI -0.55 to -0.14, I(2) 70%, 9 trials, 1543 participants), health-related quality of life (standardized MD -0.36, 95% CI -0.58 to -0.14, I(2) 50%, 3 trials, 958 participants). Subgroup analysis of pain intensity by intervention duration suggested greater pain intensity reduction with intervention periods greater than 4 weeks (MD -0.38, 95% CI -0.69 to -0.06, I(2) 0%, 6 trials, 1239 participants). CONCLUSIONS: The use of acupuncture is associated with significant reductions in pain intensity, improvement in functional mobility and quality of life. While the differences are not as great as shown by other reviews, current evidence supports the use of acupuncture as an alternative for traditional analgesics in patients with osteoarthritis. SYSTEMATIC REVIEW REGISTRATION: CRD42013005405. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1472-6882-14-312) contains supplementary material, which is available to authorized users.